The Influence Integration Processes Exert on the Intermediary System of Agricultural Enterprises - Nataliia Hurmak (Vasyl Stefanyk Precarpathian National University, 2017)
The article proves the connection between intermediary and export activities of agricultural enterprises, and indicates the influence the integration processes exert on competitiveness of domestic and foreign agricultural products. It provides a comparative characteristic of agricultural products in Ukraine and Poland. The major adverse effects caused to the selling of domestic products on foreign markets by the activities of intermediary bodies in the "producer-consumer" chain are defined.